The joint effects of ESG ratings and R&D on value relevance - Jeong-Ho Koo; Sang-Il Kim (Global Business & Finance Review (GBFR), 2023)
Purpose: Using the Ohlson model of value relevance (1995), we examine the incremental effects of the environmental, social, and governance (ESG) rating on accounting information regarding R&D expenditure. Design/methodology/approach: Samples are 3,449 firm-years of Korean manufacturing firms listed on the Korean Stock Exchange (KSE) for 2012~2021 years. We proxy the ESG activities by their ESG rating announced by the Korea Corporate Governance Service (KCGS). Our testing model is reconstructed from Ohlson's (1995) model with account- ing expenses to test whether ESG rating plays an additional role in increasing the value relevance of R&D expenses. Findings: Results show that higher ESG ratings increase the value relevance of development costs, but not research costs. The results are robust, with alternative fixed effect or double clustering, and are more relevant to those in low-technology industries or Korean non-chaebol companies. Further analyses reveal the effects of individual ESG activities that environment (E) and governance (G) increase the value relevance of capitalized development costs, but activities related to society (S) decrease value relevance. Additional test shows that voluntary disclosure additionally increases the value relevance of development cost in accounting information. Research limitations/implications: This study shows that development cost rather than research cost increases the value relevance of companies, but ESG increases the value relevance only in terms of development cost. Originality/value: We firstly show the mediating role of ESG activities in increasing the value relevance of a firm through R&D expenditure separating R&D expenditure into research expense and development costs exclusively obtained from Korean public firms.
Keywords: 650; ESG; R&D; value relevance; Ohlson model